(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The phenomenon of violence between supporters in Indonesian football competitions, especially the Indonesian League, has become a serious spotlight in the national sports world. Violence involving supporters not only tarnishes the spirit of sportsmanship but also creates an unhealthy competitive climate and threatens public safety. This study aims to examine in an educational way the factors causing violence between supporters and offer an approach to fostering sportsmanship based on Pancasila values. The method used is a qualitative approach with literature studies, field observations, and in-depth interviews with supporters, football observers, and education and sports figures. The results of the study show that violence is triggered by narrow fanaticism, weak collective emotional management, and minimal moral education in the supporter community. The application of Pancasila values ​​such as unity, just and civilised humanity, and social justice can be the foundation for building a healthy culture of sportsmanship. This study recommends the integration of character education in supporter development programs and cross-sector collaboration between clubs, government, and educational institutions to internalise the nation’s noble values ​​in the world of football. With this approach, it is hoped that Indonesian football can become a means of uniting the nation, not a trigger for conflict.